The relationship between dietary sodium intake and all-cause mortality in patients with non-alcoholic fatty liver disease: a cohort study from NHANES 2003–2018 - Li, Jiajun; Wan, Sile; Dai, Xianyu; Cui, Yifeng; Lu, Zhaoyang (Frontiers in Nutrition, 2025)
BackgroundThe relationship between sodium intake and the incidence and mortality of non-alcoholic fatty liver disease (NAFLD) is underexplored in nutritional epidemiology, highlighting the need for further research.MethodsThis longitudinal cohort study analyzed data from 13,853 Participants aged 20 and older from the National Health and Nutrition Examination Survey (NHANES) (2003–2018), including 4,465 participants with NAFLD. We collected comprehensive data on mortality, dietary sodium intake, and relevant covariates. Logistic regression assessed the relationship between sodium consumption and NAFLD incidence, while Cox regression and smooth curve fitting explored sodium intake’s link to all-cause mortality among Participants with NAFLD.ResultsAfter adjusting for confounders, logistic regression revealed a positive association between higher sodium intake and NAFLD incidence (OR = 1.16, 95% CI = 1.11, 1.21). Adjusted odds ratios for the second (Q2), third (Q3), and fourth (Q4) quartiles of sodium intake were 0.91, 1.23, and 1.52, respectively. Smooth curve fitting and threshold analysis revealed a non-linear association between sodium intake and NAFLD risk, with an inflection point at 2.49 g/d, above which NAFLD risk significantly increased. In Cox regression, sodium intake was inversely correlated with all-cause mortality in Participants with NAFLD (HR = 0.87, 95% CI = 0.80, 0.96), with adjusted hazard ratios for Q2, Q3, and Q4 being 0.79, 0.66, and 0.63, respectively. A nonlinear model indicated a threshold effect, revealing a correlation between dietary sodium intake and mortality risk (p = 0.001). We identified a threshold intake of 3.5 grams per day (equivalent to 8.9 grams of sodium chloride): below this, each unit increase in sodium intake was associated with a 16% reduction in mortality risk (HR = 0.84, 95% CI = 0.80, 0.90). For intakes above this threshold, no significant relationship with mortality risk was observed (HR = 0.99, 95% CI = 0.90, 1.08).ConclusionThis study suggests that higher sodium intake in individuals with NAFLD is associated with increased disease incidence but decreased all-cause mortality. The dose–response relationship between sodium intake and mortality risk exhibited a nonlinear pattern, with a critical inflection point around 3.5 grams per day.